Development of coronary dysfunction in adult progeny after maternal engineered nanomaterial inhalation during gestation - Sara B. Fournier (Nature Portfolio, 2021)
Abstract Maternal exposure to environmental contaminants during pregnancy can profoundly influence the risk of developing cardiovascular disease in adult offspring. Our previous studies have demonstrated impaired cardiovascular health, microvascular reactivity, and cardiac function in fetal and young adult progeny after maternal inhalation of nano-sized titanium dioxide (nano-TiO2) aerosols during gestation. The present study was designed to evaluate the development of cardiovascular and metabolic diseases later in adulthood. Pregnant Sprague–Dawley rats were exposed to nano-TiO2 aerosols (~ 10 mg/m3, 134 nm median diameter) for 4 h per day, 5 days per week, beginning on gestational day (GD) 4 and ending on GD 19. Progeny were delivered in-house. Body weight was recorded weekly after birth. After 47 weeks, the body weight of exposed progeny was 9.4% greater compared with controls. Heart weight, mean arterial pressure, and plasma biomarkers of inflammation, dyslipidemia, and glycemic control were recorded at 3, 9 and 12 months of age, with no significant adaptations. While no clinical risk factors (i.e., hypertension, dyslipidemia, or systemic inflammation) emerged pertaining to the development of cardiovascular disease, we identified impaired endothelium-dependent and -independent arteriolar dysfunction and cardiac morphological alterations consistent with myocardial inflammation, degeneration, and necrosis in exposed progeny at 12 months. In conclusion, maternal inhalation of nano-TiO2 aerosols during gestation may promote the development of coronary disease in adult offspring.